Does How You Get Paid at Work Affect Your Time off Work? The Relationship between Performance-Related Employment Contracts and Leisure Activities - Nicole Andelic; Julia Allan; Keith A. Bender; Daniel Powell; Ioannis Theodossiou (Institute of Labor Economics (IZA), 2024)
Recent research highlights the association of performance-related pay (PRP) and poor health. An uninvestigated potential mechanism is a lower frequency of leisure activities, since PRP incentives longer work hours. This study investigates PRP's effect on a variety of leisure pursuits. After correcting for self-selection, UK data show that PRP workers are less likely to engage in some forms of exercise and spend less time sleeping compared to non PRP workers. In addition, they are more likely to eat out and consume alcohol. Such leisure differences between PRP and salaried workers may negatively affect the health and wellbeing of PRP workers.
Keywords: J33; J22; I0; 330; performance-related pay; leisure; sleep; health